2013
DOI: 10.1097/01.elx.0000427103.05494.6c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin-6 and insulin resistance on early virological response of Egyptian chronic hepatitis C patients to combined pegylated interferon plus ribavirin therapy

Abstract: Background and aimResponse to hepatitis C virus (HCV)-specific therapy is variable but might be influenced by host factors. We studied whether interleukin-6 (IL-6) level, IL-6-174G4C gene polymorphism, and insulin resistance affect the response to antiviral treatment in HCV-infected patients. Patients and methods Fifty-five chronic hepatitis C patients and 13 healthy individuals as controls were included in this study. Liver function tests, HCV RNA titer, ultrasonography, and histopathological examination of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
4
1
0
Order By: Relevance
“…The serum level of interleukin-6 before treatment has been found significantly higher in HCV patients than in healthy control as shown in Table 3. This finding was in agreement with the result of El Salam, [32] and ElSerafi group [33]. These came with the result of study which done by Feldman et.al [34] who proved that HCV infection stimulate toll like receptor -2 by HCV core protein which resulted in induction of interleukin-6 and other inflammatory cytokines secretion.…”
Section: Discussionsupporting
confidence: 90%
“…The serum level of interleukin-6 before treatment has been found significantly higher in HCV patients than in healthy control as shown in Table 3. This finding was in agreement with the result of El Salam, [32] and ElSerafi group [33]. These came with the result of study which done by Feldman et.al [34] who proved that HCV infection stimulate toll like receptor -2 by HCV core protein which resulted in induction of interleukin-6 and other inflammatory cytokines secretion.…”
Section: Discussionsupporting
confidence: 90%
“…concentrations were pointedly higher in the patients than the control group, which a line with El-Serafiet al, outcomes [46] and Afzal et al [47] .…”
Section: Annals Of Tropical Medicine and Publicsupporting
confidence: 86%
“…This findings were in agreement with the results of El serafi et al [15] , who reported that CHC patients who achieved early virological response (EVR) had significantly higher IL-6 levels compared with those who did not, and IL-6 level greater than 2.15 pg/mL was significantly associated with EVR and could be considered as an independent predictor of EVR.…”
supporting
confidence: 92%
“…In total, SVR12 in naïve patients with mild fibrosis score (F1 and F2) In this study, Baseline IL-6 levels were significantly higher in patients than control group, this finding is in agreement with the result of El serafi et al [15] and Afzal et al [16] who reported that IL-6 levels were significantly higher in patients than control group.…”
supporting
confidence: 92%
See 1 more Smart Citation